Preventive Effects of Dulaglutide on Disuse Muscle Atrophy Through Inhibition of Inflammation and Apoptosis by Induction of Hsp72 Expression - Nguyen, Tram Thi Ngoc; Choi, Hojung; Jun, Hee-Sook (Frontiers in Pharmacology, 2020)
Pathological conditions such as joint immobilization, long-time bed rest, or inactivity may result in disuse-induced muscle wasting and dysfunction. To investigate the effect of dulaglutide, a long-acting glucagon-like peptide-1 receptor agonist, on disuse muscle atrophy, disuse condition was induced by spinal wire immobilization in C57BL/6 mice and the mice were treated with dulaglutide. Dulaglutide treatment effectively improved muscle function and increased muscle mass compared with vehicle treatment. Dulaglutide inhibited the decrease of muscle fiber size and the expression of atrophic factors such as myostatin, atrogin-1/MAFbx, and muscle RING-finger protein-1 in immobilized mice. In addition, dulaglutide inhibited nuclear factor kappa B activation, leading to a decrease in the mRNA levels of proinflammatory cytokines, including tumor necrosis factor-α, interleukin (IL)-1β, and IL-6 in muscle of immobilized mice. Dulaglutide suppressed the expression of apoptotic markers such as caspase-3, cleaved poly-ADP ribose polymerase, and Bax under immobilization condition and increased the expression of heat shock protein 72 (Hsp72), which is related to the amelioration of inflammation and apoptosis during disuse time. Further study showed that dulaglutide could induce Hsp72 expression via the regulation of 5-AMP-activated protein kinase signaling. Our data suggest that dulaglutide could exert beneficial effects against disuse-induced muscle atrophy.